JOURNAL OF GOVERNMENT & POLITICS : The Perception of Young Voters Towards the Integrity of the 2014 Election A Survey in Special Region of Yogyakarta - Ridho Al-Hamdi , Suranto (FISIPOL UMY, 2014)
The research examines the perception of young voters regarding the quality of the implementation the 2014 election.